Acute Encephalitis Syndrome (AES): The Case Study of Muzaffarpur District of Bihar (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: Acute encephalitis syndrome (AES); chamki fever; Muzaffarpur district; child malnutrition; hypoglycaemic encephalopathy